Wacana retorik penglipur lara Melayu: analisis struktur maklumat (Jurnal Bahasa, 2003)
This article attempts to elaborate upon information structure as an aspect in discourse focussing on Malay Folktales. The observation of information arrangement and intonation as a marker of information type, as suggested by Halliday ( 1985), was attempted on two separate folktales.